The integrated quay crane assignment and scheduling problems with carbon emissions considerations. (March 2022) - Kenan, Nabil; Jebali, Aida; Diabat, Ali
Highlights: Mathematical model for the quay crane dynamic allocation and scheduling problem. Objective is to minimize costs from operations and emissions. Considered emissions from vessels and cranes during operations, waiting, and moving. Compared two emission control policies: carbon taxation and cap-and-trade. Managerial insight and recommendations for ports. Abstract: The continuous worldwide growth in container terminals' traffic has pushed further the need for innovative research in ports' operations. The quay crane assignment and scheduling problems are the prominent focus of such research but lack, to date, carbon emission considerations despite forecasts predicting that emissions from maritime transportation will exponentially increase in the absence of regulatory policies. The objective of this paper aims at filling this gap by solving the integrated quay crane assignment and scheduling problem with consideration of carbon regulatory policies. Two mathematical models of the problem are formulated using mixed integer programming (MIP), to capture the effects of carbon taxation and carbon cap-and-trade, respectively. The sensitivity analysis conducted shows that the primary focus of a port should be minimizing the berthing time of vessels which is highly impacted by the number of QCs assigned to each vessel.